Pulling through elections by pulling the plug: Internet disruptions and electoral violence in Uganda - Lisa Garbe (Journal of Peace Research, 2023)
Does increasing Internet access and use challenge authoritarian elections? I argue that Internet access provides both opposition supporters and government authorities with new means to shape electoral conduct. Opposition supporters can use the Internet to report on electoral malpractice and mobilize for support. At the same time government authorities can use the Internet to monitor antiregime sentiment prior to the elections and disrupt Internet access to selectively repress regime opponents during the elections. Studying Uganda's 2016 presidential elections, evidence from election monitoring and survey data suggests that electoral violence is significantly higher in opposition strongholds with greater Internet access prior to the Internet disruption and is targeted specifically at voters. Insights from qualitative interviews with politicians, journalists and activists underline that the disruption of Internet access indeed hindered opposition supporters to effectively challenge electoral malpractice. Overall, the results stress the important role that Internet access can play for opposition actors in authoritarian elections. At the same time, they highlight their susceptibility to manipulation by government authorities.
Keywords: 320; authoritarian elections; electoral violence; social media; sub-Saharan Africa